HUBUNGAN KESEGARAN JASMANI DENGAN HASIL BELAJAR SISWA KELAS V SDN 006 TERATAK RENDAH KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Amhelisjon Amhelisjon; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, based on the observation while researchers do are mostly students of class V SDN 006 Teratak Rendah Subdistrict Logas Tanah Darat yet have good physical fitness, resulting in decreased student learning outcomes. Therefore, researchers interested in conducting research on the physical fitness with student learning outcomes SDN 006 Teratak Rendah Subdistrict Logas Tanah Darat. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is a physical fitness while the dependent variable (Y) is the result of learning. The sample in this study were students of SDN 006 Teratak Rendah Subdistrict Logas Tanah amounting to 8 people with a total sampling using sampling. Data obtained through measurement using a physical fitness test TKJI with 5 items and the results obtained from the study subjects the value of MID half penjaskesrek. After the data obtained by data analysis using product moment correlation that previously normality test data using test Liliefors. Based on data analysis L count <L table which means the normal distribution of data, folRendahed by correlation values obtained rhitung = 0.372 while rtable = 0707 Then it can be concluded as folRendahs: There was no relationship between physical fitness to learning outcomes Student Class V SDN 006 Rendah Teratak District of Logas Tanah Darat.Keywords: Physical Freshness, Learning Outcomes